Early repatriation post-thrombectomy: a model of care which maximises the capacity of a stroke network to treat patients with large vessel ischaemic stroke. (15th April 2020) - Griffin, Emma; Murphy, Sean; Sheehan, Mark; Power, Sarah; Brennan, Paul; O'Hare, Alan; Looby, Seamus; McWilliams, Sebastian; Moynihan, Barry; Williams, David; Boyle, Karl; O'Neill, Damien; et al.
Abstract : Background and purpose: Healthcare systems are challenged to provide access to thrombectomy in acute stroke patients. Either the "drip and ship" or "mothership" models result in increased numbers of patients in the endovascular stroke centre (ESC). We describe our approach for a "drip, ship, retrieve and leave" model repatriating patients immediately or within 24 hours of thrombectomy. Methods: We included consecutive patients who underwent thrombectomy from January 2016 to June 2018. Patients from local region primary stroke centres (PSC) are immediately repatriated and those from remote region PSCs are admitted for 24 hours before repatriation. Key parameters recorded included clinical, radiological and timeline data as well as 90-day modified Rankin Scale (mRS). Patients who stayed beyond the intended time period in the ESC were analysed. Results: From January 2016 to June 2018, 435 patients were transferred, with 352 patients in the local region group and 83 in the remote region group. The median NIHSS was 16 with a median ASPECTS of 9. Good functional outcome was seen in 47% of patients with a mortality rate of 19%. The local region group that were repatriated at the intended time period had a 90-day mRS 0–2 of 47% compared with 20% of those admitted to the ESC (P=0.006). Mortality rates were 20% and 27% respectively (P=0.377). The remote region group, repatriated at 24 hours' post-emergency endovascular thrombectomy had 90-day mRS 0–2 of 65% compared with 41% in the group admitted (P=0.042). Mortality rates were 4% and 22% respectively (P=0.007). Conclusion: This model enables the treatment of large numbers of patients with large vessel occlusion acute ischaemic stroke with thrombectomy within a national stroke service and system of care which would not otherwise be facilitated.